2005
DOI: 10.1103/physrevb.71.245112
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution soft x-ray photoelectron study of density of states and thermoelectric properties of the Heusler-type alloys(Fe23V13

Abstract: The high-resolution soft x-ray photoelectron study of Heusler͑L2 1 ͒-type ͑Fe 2/3 V 1/3 ͒ 100−y Al y ͑y = 23.8− 25.8͒ alloys directly confirms the correlation between their thermoelectric properties and the electronic structures near the Fermi level. It shows the rigid-band-like shift of the main 3d bands and the increase of the photoelectron intensity at the Fermi edge with the small deviation of the Al content from stoichiometry, i.e., y = 25.0. This implies the existence of the pseudogap across the Fermi le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
3
14
0
1
Order By: Relevance
“…To date, theoretical and experimental studies [6][7][8][9] have shown that Fe 2 VAl possesses a nonmagnetic semimetallic electronic band structure with a sharp pseudogap around the Fermi energy E F , as observed in Fig. 1, where the electronic band structure and density of states (DOS) are calculated using the WIEN2k code 10,11) .…”
Section: Introductionmentioning
confidence: 99%
“…To date, theoretical and experimental studies [6][7][8][9] have shown that Fe 2 VAl possesses a nonmagnetic semimetallic electronic band structure with a sharp pseudogap around the Fermi energy E F , as observed in Fig. 1, where the electronic band structure and density of states (DOS) are calculated using the WIEN2k code 10,11) .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 compares typical valence-band spectra of some of studied alloys. The stoichiometric alloy Fe 2 VAl with small but positive thermoelectric power shows a small shoulder structure at E F in the photoelectron spectrum, indicating the pseudogap predicted for the alloy as having a semimetallic band structure [6]. A small shoulder structure around E F , indicative of the pseudogap, is also recognized for the n-type thermoelectric alloys with the excess V (x > 0).…”
Section: Methodsmentioning
confidence: 71%
“…Theoretical and experimental studies [3,4] show that an intermetallic compound Fe 2 VAl possesses a sharp pseudogap across the Fermi energy E F , which may lead to the enhancement of the thermoelectric power by changing E F position on partial substitution of the forth element with more or less valence electrons than the original constituent elements without altering the valence-band electronic structure (so-called rigid band model) [5], because the thermoelectric power S(T) at temperature T may depend on the electronic density of states N(E) as follows [6]; ( ) ( )( ) ( ) electron counts per constituent atom (VEC) [5], which can be semi-quantitatively explained by equation (1) [4,6]. However, the off-stoichiometric Fe/V change results in quite different dependence of the thermoelectric power on VEC in a non-rigid-band-like manner and its further enhancement [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…When Fe was replaced by V, the conduction shifted from p-type to ntype, while the Seebeck coefficient and low-temperature electrical conductivity increased sharply [7]. Other research showed that the Seebeck coefficient of Fe 2 VAl was also sensitive to Al content [8]. The Seebeck coefficient shifted from −130 to 75 V/K with the deviation of the Al content in (Fe 2/3 V 1/3 ) 100−y Al y (23.8 ≤ y ≤ 25.8) alloys [8].…”
Section: Introductionmentioning
confidence: 95%